Knowledge, attitude and practices about hemovigilance among practitioners: a cross-sectional study - ., Roshi; Tandon, Vishal R. (International Journal of Basic & Clinical Pharmacology, 2019)
Abstract: Transfusion by blood and blood products forms an important part of treatment. But this is not free from transfusion reactions which may be in the form of fever, rashes, shivering, anaphylaxis or even death. Hemovigilance is a programme of reporting such events. Materials and Methods: The present study was conducted in a tertiary care hospital of Jammu, (J& K). Permission was taken from Institutional Ethics Committee, Govt. Medical College, Jammu. A pretested questionnaire was prepared and circulated among practitioners. They were given time of 15 minutes to fill that questionnaire. After 15 minutes, the filled questionnaire were collected and were analysed. The data was presented in tabulated form. Results: Total 50 practitioners were included in the study. All the practitioners had knowledge about transfusion reactions. Only 10% of the practitioners had knowledge that transfusion reactions can be prevented, 40% of the practitioners had knowledge about hemovigilance programme and had an idea that transfusion reactions can be reported. But only 10% of the practitioners knew where to report and who can report, 6% knew how to report. Only 48% of the practitioners thought that transfusion reactions should be reported, 70% of the practitioners thought that transfusion reactions can be dangerous. 40% of practitioners told that seminars/CMEs should be planned. 80% of practitioners had encountered transfusion reactions, but only 2% had documented the same. 10% of the practitioners had attended seminars, CMEs. Many reasons were quoted for not reporting transfusion reactions. Conclusion: Overall, most of the practitioners have a positive attitude towards transfusion reaction reporting but knowledge regarding the haemovigilance concept is poor and the majority of them never reported such reaction. Hence, our study demands increased awareness and continued training to strengthen the haemovigilance system.